Analisis Pengaruh Bunga Kredit dan Jangka Waktu Pengembalian Pinjaman Terhadap Profitabilitas Usaha Di Koperasi Kredit Citra Hidup Tribuana Kalabahi Kabupaten Alor - Junius M. Sau Sabu (Peneliti.net, 2021)
The purpose of this study was to obtain empirical evidence regarding the effect of loan interest and loan repayment terms on business profitability at the Citra Life Credit Cooperative Tribuana Kalabahi, Alor Regency. The method used in this research is multiple linear regression analysis method with the help of SPSS version 22 program. The results show that the loan interest variable and the repayment period variable partially or simultaneously affect the Business Profitability variable in the Citra Hidup Credit Cooperative Tribuana Kalabahi, Alor Regency. . Research also proves that the value of R Square (R2) is 41.9%. This shows that 41.9% of the dependent variable can be explained or explained by the independent variable. Meanwhile, 58.1% of the dependent variable was explained by other factors that were not used in this research model